Reforma regulatoria energética en Europa: impacto de los cambios de control corporativo sobre el valor de las empresas (2012)
The deregulation process of the European power sector generated strategic moves by the power companies leading to a complete reordering of the European electric market that brought out an upsurge of mergers and acquisitions. This paper researches how the following wave of mergers and acquisitions that took place in the 2000 impacted the market value for the acquiring and selling companies that took part of it. With this objective and making use of the event study methodology, and OLS, GARCH, and SURE econometric techniques, we found that mergers and acquisitions had a positive and significant effect on the average market price in public stock exchanges for the companies that were target which is consistent with previous studies.